Ultrasound-assisted extraction of polysaccharide from Allium chinense G. Don epidermal waste: Evaluation of extraction mechanism, physicochemical properties, and bioactivities - Jiangfei Li; Guanjun Ye; Zhilong Zhou; Jianlong Wang; Jiayu Wang; Ting Ju; Alejandro Cifuentes; Elena Ibañez; Denis Baranenko; Haitian Zhao; Weihong Lu (Ultrasonics Sonochemistry)
Allium chinense G. Don waste (ACGD) has an abundance of polysaccharides (ACGDP). Therefore, in this study, a method for extraction of ACGDP from ACGD by ultrasonic-assisted hot water extraction (UAE) based on ultrasonic cleaning equipment was developed. It was compared with hot water extraction (HWE) in terms of efficiency, energy consumption, and carbon emissions. Then, the mechanism of efficient extraction of ACGDP by UAE was further investigated. Finally, the physicochemical properties and in vitro activity of ACGDP were evaluated. The results suggested that the optimal conditions of UAE were temperature 53 ℃, time 34 min, power 280 W, liquid–solid ratio 22 mL/g, and the yield of ACGDP was 30.08 ± 0.21 %. Compared with HWE, UAE yield was increased by 30.10 %, time was shortened by 71.50 %, energy consumption was reduced by 77.33 %, and CO2 emission was reduced by 82.56 %. UAE can efficiently extract ACGDP by changing the composition of the cell wall, destroying the microstructure, and reducing the particle size. In addition, ACGDP had better thermal stability and antioxidant activity, and exhibited positive hypoglycemic activity. Overall, this study provided a theoretical basis and new insights into the efficient extraction mechanism of UAE and the high-value utilization of ACGD waste.